PENENTUAN KADAR NITRIT PADA KANGKUNG MENGGUNAKAN SPEKTROFOTOMETRI UV-VISIBLE - Kuntari Kuntari; Popi Yuliana; Thorikul Huda (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
The method of determining the nitrite content of water spinach has been conducted using UV-Visible spectrophotometry. The purpose of this research is to determine nitrite level in water spinach and to test linearity, precision, limit of detection (LOD) and limit of quantification (LOQ) for uv-visible spectrophotometry. Based on the linearity test, the equation of the line y = 1.076x + 0.0201 is obtained with a coefficient of determination (R2) of 0.9995. In determining precision, the value of nitrite level is 0,0740 mg/Kg with % RPD value is 16.71%. The LOD value of 0,0485 mg/L NaNO2 and LOQ value of 0,1617 mg/L NaNO2. Based on these results, improvements need to be made so that the sample concentration is above the LOD so that the nitrite level can be measured accurately and pricise.